2022
DOI: 10.3390/pr10020365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Novel Extraction Strategies on the Recovery of Phenolic Compounds and Associated Antioxidant Properties from Buckwheat Hull (Fagopyrum esculentum)

Abstract: This study investigated the effects of novel extraction technologies, including ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), pulsed electric field (PEF), high-pressure processing (HPP), enzyme-assisted extraction (EAE), and conventional extraction, on the recovery of phenolic compounds and associated antioxidant properties from buckwheat hull (Fagopyrum esculentum). Initially, twenty-four extraction strategies were investigated. Based on the results of the total phenolic content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Other authors have also confirmed that BH is an excellent source of phenolic and antioxidant compounds, mainly anthocyanins, flavanones, flavanol, flavones, flavonols, and phenolic acids [49]. Recently, Noore et al [50] identified 41 phenolic compounds in BH. BH is especially rich in phenolics such as protocatechuic acid, hyperoside, vitexin, isovitexin, and rutin (in increasing order) [51].…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 93%
“…Other authors have also confirmed that BH is an excellent source of phenolic and antioxidant compounds, mainly anthocyanins, flavanones, flavanol, flavones, flavonols, and phenolic acids [49]. Recently, Noore et al [50] identified 41 phenolic compounds in BH. BH is especially rich in phenolics such as protocatechuic acid, hyperoside, vitexin, isovitexin, and rutin (in increasing order) [51].…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 93%
“…An example of the bio-based material that has not yet been studied as the filler for UF resin in plywood production is buckwheat husk. Buckwheat belongs to the Polygonaceae family, and the two most cultivated species are Fagopyrum tataricum and Fagopyrum esculentum [24]. It is widely cultivated around the world mainly for food production due to its high content of proteins, amino acids, fibre, vitamins and minerals [25].…”
Section: Introductionmentioning
confidence: 99%
“…Noore et al (2022) [4] investigated the influence of different extraction strategies, including conventional extraction and novel technologies such as ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), pulsed electric field (PEF), high pressure processing (HPP), and enzyme-assisted extraction (EAE), on the recovery of phenolic compounds (liquid chromatography-mass spectrometry LC-MS, and Folin-Ciocalteau method) and associated antioxidant properties (DPPH and FRAP) from buckwheat hull (Fagopyrum esculentum). Forty-one phenolic compounds belonging to eleven different groups including anthocyanins, flavanols, flavanones, flavones, flavonols, phenolic acids, isoflavones, lignans and quinones were identified in the extracts.…”
mentioning
confidence: 99%